2016
DOI: 10.1186/s12978-016-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Inequalities in the coverage of place of delivery and skilled birth attendance: analyses of cross-sectional surveys in 80 low and middle-income countries

Abstract: BackgroundHaving a health worker with midwifery skills present at delivery is one of the key interventions to reduce maternal and newborn mortality. We sought to estimate the frequencies of (a) skilled birth attendant coverage, (b) institutional delivery, and (c) the combination of place of delivery and type of attendant, in LMICs.MethodsNational surveys (DHS and MICS) performed in 80 LMICs since 2005 were analyzed to estimate these four categories of delivery care. Results were stratified by wealth quintile b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 45 publications
3
60
0
Order By: Relevance
“…26,27 This is confirmed by our finding of an average difference greater than 50 percentage points between the 2 extremes of the wealth distribution in all surveys. We point out that similar magnitudes of absolute gaps may represent very different inequality patterns.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…26,27 This is confirmed by our finding of an average difference greater than 50 percentage points between the 2 extremes of the wealth distribution in all surveys. We point out that similar magnitudes of absolute gaps may represent very different inequality patterns.…”
Section: Discussionsupporting
confidence: 78%
“…Information on skilled birth attendants was available in a smaller number of surveys, and results were virtually identical to those for coverage with institutional deliveries as expected because of the high correlation between the 2 indicators (Pearson's r = 0.956; P < .001). 27 These results are available upon request.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The situation is even worse when it comes to pregnant women in developing countries where deliveries are not most of times attended by skilled health professionals with obvious poor-rich inequalities [3]. Cross-sectional surveys in 80 low and middleincome countries have shown inequalities in the coverage of place of delivery and skilled birth attendance (SBA): SBA deliveries at home and facility non-SBA deliveries were more common in rural than in urban areas and among the poorest in all concerned regions including Sub-Saharan Africa [4]. Another multi-country study showed that only 17.7% of the poorest women versus 54.1% of the richest women used public facilities in Sub-Saharan Africa; and among home births in the poorest, 56% were unattended whereas 41% were attended by a traditional birth attendant [5].…”
Section: Introductionmentioning
confidence: 99%